Overview of standards related to the occupational risk and safety of nanotechnologies - Ramos, Delfina (2022)
Nanomaterials offer new technical and commercial opportunities but, due to their low particle size, raise occupational health and safety concerns and may also pose risks to the consumers and the environment. In the last 15 years, many standards have been developed in the area of nanotechnologies, taking into account, namely, occupational risk and safety. This paper presents an overview of the standards in this area, with special emphasis at the ISO level, but also at European level, where standards are considered as an important support for legislation. A brief presentation of five relevant ISO standards is included. Relevant European Standards are also mentioned. The control banding approach for occupational risk management applied to engineered nanomaterials, according to ISO/TS 12901-2:2014, is presented. Standards are essential for society and should, in fact, be considered an important tool for companies to support sustainable products and process innovation.